Structural breaks in global stock markets: Are they caused by pandemics, protests or other factors? - Joshua A. Ndako; Terver T. Kumeka; Festus Fatai Adedoyin; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The aim of this study is to examine the impact of the COVID-19 pandemic and other similar global events on the global stock market. The data used covers 16 countries of the world and a series of quarterly data ranging from 1919Q1 to 2020Q2 for major stock market index was used. The Bai and Perron's multiple structural break approach were adopted. Different number of break dates is noticed across several regions. While selected sample countries in Europe have at least ten break dates under the period of investigation, we observe for US, Canada and Australia, only twelve break dates. Asia and the other bloc of countries report ten and twelve break dates respectively. Notably, one most prominent causes of structural changes in stock markets (with the exclusion of Germany) appears to be from the GFC, which had inverse effects on major market around the world. The most prominent source of structural breaks in the Asian markets appears to be from the 2008-2009 GFC. In addition, we found evidence of structural breaks in several stock markets in the world, resulting from the 2009-2010 Global Pandemic, that is, the H1N1 virus/pigs Swine Flu; 2003 SARS; MERS; and EBOLA. In addition, as explained above, events have the tendency of unfolding over time; hence matching exact breaks in stock market data to precise events is very unlikely.
Keywords: 330; Pandemics; Stock Market Index; Structural Breaks; Bai and Perron multiple break; Global events